2016
DOI: 10.1073/pnas.1522376113
|View full text |Cite
|
Sign up to set email alerts
|

Club cells surviving influenza A virus infection induce temporary nonspecific antiviral immunity

Abstract: A brief window of antigen-nonspecific protection has been observed after influenza A virus (IAV) infection. Although this temporary immunity has been assumed to be the result of residual nonspecific inflammation, this period of induced immunity has not been fully studied. Because IAV has long been characterized as a cytopathic virus (based on its ability to rapidly lyse most cell types in culture), it has been a forgone conclusion that directly infected cells could not be contributing to this effect. Using a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 32 publications
1
53
1
Order By: Relevance
“…Both immune and epithelial cells sense IAV in vivo (40), and responses can be dependent on the cell type. We have previously demonstrated that club cells, which survive virus replication, exhibit prolonged ISG signatures (41,42). Our data demonstrate that IAV tropism changes over the course of infection.…”
Section: Discussionsupporting
confidence: 55%
“…Both immune and epithelial cells sense IAV in vivo (40), and responses can be dependent on the cell type. We have previously demonstrated that club cells, which survive virus replication, exhibit prolonged ISG signatures (41,42). Our data demonstrate that IAV tropism changes over the course of infection.…”
Section: Discussionsupporting
confidence: 55%
“…The cell lines were not routinely monitored for mycoplasma. The Cre-Reporter cassette was constructed and transduced into A549 cells as previously described (Hamilton et al, 2016). Validation of the screening cell line is described in the supplemental information.…”
Section: Methodsmentioning
confidence: 99%
“…ELISAs were performed as previously described (Hamilton et al, 2016) and are detailed in the Supplemental Experimental Procedures. The quantity of 9H10 antibody per egg was calculated by multiplying the total volume of allantoic fluid per egg by the concentration of the antibody.…”
Section: Elisa and Microneutralization Assaymentioning
confidence: 99%